Development and Characterization of a Novel Non-Lytic Cancer Immunotherapy Using a Recombinant Arenavirus Vector Platform - Lauterbach, Henning; Schmidt, Sarah; Katchar, Kia; Qing, Xiaoping; Iacobucci, Corinne; Hwang, Andy; Schlienger, Katia; Berka, Ursula; Raguz, Josipa; Ahmadi-Erber, Sarah; Schippers, Timo; Stemeseder, Felix; et al. (Frontiers in Oncology, 2021)
Engineered viral vectors represent a promising strategy to trigger antigen-specific antitumor T cell responses. Arenaviruses have been widely studied because of their ability to elicit potent and protective T cell responses. Here, we provide an overview of a novel intravenously administered, replication-competent, non-lytic arenavirus-based vector technology that delivers tumor antigens to induce antigen-specific anti-cancer T cell responses. Preclinical studies in mice and cell culture experiments with human peripheral blood mononuclear cells demonstrate that arenavirus vectors preferentially infect antigen-presenting cells. This, in conjunction with a non-lytic functional activation of the infected antigen-presenting cells, leads to a robust antigen-specific CD8+ T cell response. T cell migration to, and infiltration of, the tumor microenvironment has been demonstrated in various preclinical tumor models with vectors encoding self- and non–self-antigens. The available data also suggest that arenavirus–based vector therapy can induce immunological memory protecting from tumor rechallenge. Based on promising preclinical data, a phase 1/2 clinical trial was initiated and is currently ongoing to test the activity and safety of arenavirus vectors, HB-201 and HB-202, created using lymphocytic choriomeningitis virus and Pichinde virus, respectively. Both vectors have been engineered to deliver non-oncogenic versions of the human papilloma virus 16 (HPV16) antigens E7 and E6 and will be injected intravenously with or without an initial intratumoral dose. This dose escalation/expansion study is being conducted in patients with recurrent or metastatic HPV16+ cancers. Promising preliminary data from this ongoing clinical study have been reported. Immunogenicity data from several patients demonstrate that a single injection of HB-201 or HB-202 monotherapy is highly immunogenic, as evidenced by an increase in inflammatory cytokines/chemokines and the expansion of antigen-specific CD8+ T cell responses. This response can be further enhanced by alternating injections of HB-202 and HB-201, which has resulted in frequencies of circulating HPV16 E7/E6-specific CD8+ T cells of up to 40% of the total CD8+ T cell compartment in peripheral blood in analyses to date. Treatment with intravenous administration also resulted in a disease control rate of 73% among 11 evaluable patients with head and neck cancer dosed every three weeks, including 2 patients with a partial response.